Targeting and Managing Behavioral Symptoms in Individuals with Dementia: A Randomized Trial of a Nonpharmacologic Intervention - Gitlin, Laura N. (2010)
OBJECTIVES: Test effects of an intervention that helps families manage distressful behaviors. DESIGN: Two-group randomized trial SETTING: In-home PARTICIPANTS: 272 caregivers and dementia patients INTERVENTION: Up to 11 home/telephone contacts over 16-weeks by health professionals who identified potential triggers of patient behaviors including communication, environment, patient undiagnosed medical conditions (by obtaining blood/urine samples), and trained caregivers in strategies to modify triggers and reduce caregiver upset. Between 16–24 weeks, 3 telephone contacts reinforced strategy use. MEASUREMENTS: Primary outcomes included frequency of targeted problem behavior, and caregiver upset with and confidence managing it at 16-weeks. Secondary outcomes included caregiver well-being and management skills at 16 and 24 weeks, and caregiver perceived benefits. Prevalence of medical conditions for intervention patients were also examined. RESULTS: At 16 weeks, 67.5% of intervention caregivers reported patient improvement in targeted problem behavior compared to 45.8% of caregivers in a no-treatment control group (p=.002), reduced upset with (p=.028) and enhanced confidence managing (p=.011) the behavior. Additionally, compared to controls, intervention caregivers reported less upset with all problem behaviors (p=.001), negative communication (p=.017), burden (p=.051), and improved well-being (p=.001). Fewer intervention caregivers had depressive symptoms (53.0%) than control group caregivers (67.8%, p=.020). Similar caregiver outcomes occurred at 24-weeks. Compared to controls, intervention caregivers perceived more study benefits (p values <.05) including ability to keep patients home. Blood/urine samples of intervention patients showed 40 (34.1%) had undiagnosed illnesses requiring physician follow-up. CONCLUSION: Targeting behaviors upsetting to caregivers and modifying potential triggers improves patient symptomatology and caregiver well-being and skills.